2021
DOI: 10.48550/arxiv.2110.04132
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variability of the Reconnection Guide Field in Solar Flares

Joel T. Dahlin,
Spiro K. Antiochos,
Jiong Qiu
et al.

Abstract: Solar flares may be the best-known examples of the explosive conversion of magnetic energy into bulk motion, plasma heating, and particle acceleration via magnetic reconnection. The energy source for all flares is the highly sheared magnetic field of a filament channel above a polarity inversion line (PIL). During the flare, this shear field becomes the so-called reconnection guide field (i.e., the non-reconnecting component), which has been shown to play a major role in determining key properties of the recon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 63 publications
(92 reference statements)
2
8
0
Order By: Relevance
“…It indicates that flare reconnection likely starts with a strong guide field in the early phase, and reconnection then proceeds at higher altitudes with the ever weakening guide field. Using high-resolution 3D MHD simulations, Dahlin et al (2021) have reproduced such strong-to-weak shear evolution observed in flare ribbons or loops (e.g. Qiu et al, 2017, and references therein), and confirmed its association with the variation of the guide field in the reconnection current sheet that cannot be directly measured in observations.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…It indicates that flare reconnection likely starts with a strong guide field in the early phase, and reconnection then proceeds at higher altitudes with the ever weakening guide field. Using high-resolution 3D MHD simulations, Dahlin et al (2021) have reproduced such strong-to-weak shear evolution observed in flare ribbons or loops (e.g. Qiu et al, 2017, and references therein), and confirmed its association with the variation of the guide field in the reconnection current sheet that cannot be directly measured in observations.…”
Section: Introductionmentioning
confidence: 63%
“…Su, Golub, and Van Ballegooijen, 2007;Yang et al, 2009, and references therein), and also demonstrated in magnetohydrodynamic simulations (e.g. Aulanier, Janvier, and Schmieder, 2012;Dahlin et al, 2021). Finally, HXR maps have been obtained using the Pixon method at two energies, 25 -50 keV and 12 -25 keV, and are superimposed with the AIA images in Figure 1c and Figure 1d, respectively.…”
Section: Overview Of Observations: Eruptive Flares and Confined Flaresmentioning
confidence: 80%
See 1 more Smart Citation
“…In principle, the eruption could be determined by sufficiently accurate observations of the free energy buildup and the resulting filament channel structure. Three general processes have been proposed for filament channel formation (see Mackay 2015): shear flows and/or the closely related helicity condensation model (Antiochos 2013;Dahlin et al 2021), flux cancellation (Gaizauskas 1998;Wang & Muglach 2007), and flux emergence (Manchester et al 2004a;Fan 2009). The key point here, as reviewed in Patsourakos et al (2020), is that the ideal eruption mechanisms require that the filament field have sufficient twist to trigger a kink-like or torus instability (Shafranov 1956;Chen 1989;Kliem & Török 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Classic examples of this approach to investigating solar eruptions have been the many simulations of the Magnetic Breakout Model, which uses reconnection as the eruption mechanism (Antiochos 1998;. In typical Breakout simulations magnetic energy is built up in the corona by prescribed surface motions at the lower boundary, either large-scale shearing flows (e.g., Karpen et al 2012) or small-scale randomized motions leading to helicity condensation (e.g., Dahlin et al 2021). The normal component of the coronal field is held fixed at this lower boundary, which is presumed to represent the high-beta photosphere, and the coronal flux is assumed to be multipolar so that a separatrix surface and null point are present.…”
Section: Introductionmentioning
confidence: 99%